2019
DOI: 10.3390/cancers11081154
|View full text |Cite
|
Sign up to set email alerts
|

Association between Circulating Fibroblast Growth Factor 21 and Aggressiveness in Thyroid Cancer

Abstract: Fibroblast growth factor 21 (FGF21) plays important roles in regulating glucose, lipid, and energy metabolism; however, its effects in tumors remain poorly understood. To understand the role of FGF21 in regulating tumor aggressiveness in thyroid cancer, serum levels of FGF21 were measured in healthy subjects and patients with papillary thyroid cancer (PTC), and expression levels of FGF21, FGF receptors (FGFRs), and β-klotho (KLB) were investigated in human thyroid tissues. The cell viability, migrating cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…Kang et al showed that FGF21 was highly expressed in papillary thyroid carcinoma serum and that its expression level was positively correlated with the tumor stage, vascular lymphatic invasion, and recurrence. The underlying mechanism proposed was that FGF21 promotes tumor growth and invasion through the regulation of the signal axis of the FGFR pathway [49]. Studies in China reported that the transient silencing of FGF21 increased the sorafenib-induced inhibition of hepatocellular carcinoma cell proliferation [50].…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al showed that FGF21 was highly expressed in papillary thyroid carcinoma serum and that its expression level was positively correlated with the tumor stage, vascular lymphatic invasion, and recurrence. The underlying mechanism proposed was that FGF21 promotes tumor growth and invasion through the regulation of the signal axis of the FGFR pathway [49]. Studies in China reported that the transient silencing of FGF21 increased the sorafenib-induced inhibition of hepatocellular carcinoma cell proliferation [50].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of PTC cell lines with recombinant FGFR1 leads to FGFR pathway signaling activation, leading to ERK and AKT phosphorylation, EMT, and to the development of a more aggressive phenotype of tumor cells. Thus, FGFR1 can promote invasion and migration of PTC cells ( 136 ). Parascandolo et al showed that mesenchymal stem cell (MSC) cultures derived from non-tumorigenic thyroid tissues and from PTCs, exposed to cancer cell-released factors, are able to differentiate into a multitude of cell types, including CAFs, which eventually support tumor progression.…”
Section: Influence Of the Tumor Microenvironment On Tcscsmentioning
confidence: 99%
“…In addition, FGF21 is also expressed in other tissues such as the pancreas, adipose tissue, muscle, and kidney under pathological and stress conditions 11 . Recent studies have also revealed that FGF21 is associated with the occurrence and development of tumors such as colon cancer 12 , thyroid cancer 11 , and liver cancer 13 . However, its role in PCa has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%